A broadly sampled 3-loci plastid phylogeny of Atraphaxis (Polygoneae, Polygonoideae, Polygonaceae) reveals new taxa: III. A. kuvaevii and сryptic species in A. pungens from Southern Siberia and Northern Mongolia - Yurtseva, Olga V.; Vasilieva, Natalia V.; Kostikova, Vera A.; Samigullin, Tahir H. (Phytotaxa, 2022)
Maximum Likelihood (ML) and Bayesian analyses (BI) applied for combined plastid matrix (cpDNA trnL(UAA) intron, trnL–trnF IGS, and rpl32–trnL(UAG) IGS regions) of 124 accessions of 36 species of the genus Atraphaxis have shown new species from southern Siberia. The analysis of 112 accessions of 36 species of nrDNA ITS1–5.8S–ITS2 regions showed less clear topology. A new species A. kuvaevii endemic for Yenisey Valley in Tuva was revealed with molecular and morphological data. The plants attributed previously to A. pungens split into three cryptic species with different plastid regions. A. pungens grows in the south of Krasnoyarskii Krai, Khakassia, Tuva and Mongolia. A. ledebourii is distributed in Altai Mts, Tuva and Mongolia. It combines a functional ITS ribotype and a psedogenized ribotype, what agrees with high chromosome numbers. The third pseudogenized ribotype shared with A. ariana was found in a single sample from SE Tuva. A. ×uyukensis is a species of hybrid origin from the Uyuk ridge with the ITS ribotype of A. pungens, which probably captured cpDNA of unknown species related to A. selengensis and A. davurica by maternal lineage. Despite the differences in plastid regions, these cryptic species have no clear morphoplogical distinctions. The hybrid A. pungens × A. ledebourii from Tuva and the hybrid A. ledebourii × A. pungens from Hangay Mts in Mongolia do not differ from the parents. The eastern race of A. frutescens s.l. sub A. decipiens from Tuva and Altai Republics differs from the western race of A. frutescens with a single nucleotide substitution in cpDNA trnL–trnF IGS, a distinct ITS ribotype, a short perianth tube equal to outer tepals, herbaceous tubular ochreolas and linear-lanceolate leaf blades. The hybrids A. pungens × A. decipiens and A. decipiens × A. pungens were detected in three locations in Tuva. Cryptic hybrids A. ledebourii × A. decipiens, A. ledebourii × A. frutescens, and A. decipiens × A. ledebourii were detected in Altai and Tuva Republics. Two hybrids A. decipiens × A. ledebourii have shown the capture of cpDNA of A. decipiens. Atraphaxis laetevirens is limited by the territory of Kazakhstan, Altai Republic and Dzungaria and does not grow in Tuva and Khakassia.